A Case Study on Farmers’ Literacy in Agriculture Information in Lunglei District, Mizoram (Indian Journal of Extension Education, 2024)
Many farmers in Lunglei District depend on agriculture for their living, therefore urban residents also depend on agricultural produce. Due to the development of technology, farmers today have easy access to a variety of information that they can use in their farming. However, they still need to know where to turn for reliable data that they can use. The present study adopted a quantitative research method for accessing the information on literacy awareness among 150 agricultural farmers in selected 30 villages in Lunglei District, Mizoram during 2020-2023. The majority of the farmers claimed to be information literate, the findings show that farmers lacked information literacy abilities. Farmers rely heavily on the information they learn from other people, have poor reading abilities, and are unable to search for the information they require. The use of media has been discovered to be the most effective platform for farmers to acquire information and farmers primarily seek information to determine whether forecasts are accurate. The result suggested that farmers must be instructed on how to improve their information literacy abilities by Government officials and library professionals. carrots, sugarcane, chillies, ginger, tobacco, pineapple, and potatoes. Lunglei is located in the heart of Mizoram. According to the 2011 census, the entire area is 4536 square kilometres, and there are 1, 61, 428 people living there, of whom 78, 537 are women and 82, 891 men. The literacy rate is 88.86 per cent. Approximately 65–70 per cent of the population works in agriculture, making it the most common industry. Lunglei is separated into three R.D. Blocks: Lunglei, Bunghmun, and Lungsen; two major sub-districts: Tlabung SDO (S) and Lunglei SDO (S). The administrative hub of the district is located in Lunglei town.